EXAMINATION OF THE EFFECTS OF LOGISTICS CAPABILITIES AND LEARNING ORIENTATION ON FINANCIAL AND GROWTH PERFORMANCE AND EXPORT PERFORMANCE IN EXPORT-ORIENTED COMPANIES - Sönmez Çakır, Fatma; Zehir, Songul; Adıguzel, Zafer (My University, 2022)
The research was conducted to examine the effect of logistics skills and learning orientation on performance outcomes in exporting foreign trade companies operating in Istanbul. The reason for choosing these companies is that logistics capabilities become more important in exporting companies in terms of logistics performance and financial and growth performance. A sample of 983 participants was taken to establish and test the model, and a scale consisting of a total of 43 statements was presented to them. Analyzes were performed using SmartPLS 3.3.5. For a good organizational performance, export-oriented companies should attach importance to learning orientation and have logistics capabilities in order to constantly improve themselves. In the research, it is supported by hypotheses that the logistics capabilities and learning orientation of export-oriented companies positively affect both their logistics performance and their financial and growth performances. The research is innovative in that it collects data from export-oriented companies and examines both their logistics capabilities and learning orientations. The sample group consists of export-oriented companies operating in Istanbul. For this reason, it would be correct to evaluate the results obtained in the research only in terms of export-oriented companies and not to generalize.
Keywords: Financial; Logistics Capabilities; Learning Orientation; Growth Performance; Export Performance